Critical speed & critical stroke rate could be useful physiological and technical criterial for coaches to monitor endurance performance in competitive swimmers - Pelayo, P.; Dekerle, J.; Delaporte, B.; Gosse, N.; Sidney, M. (coachesinfo.com, 2000)
The purposes of this study were to determine whether the concepts of critical swimming speed (CSS) and critical stroke rate (CSR) could be reliable and used by coaches in order to control and monitor endurance performance in competitive swimmers. The results of this study conducted with well-trained swimmers showed that CSS could be determined easily from two common distances and more accurately from 200- and 400-m tests after a correction of minus 1.4%. Moreover, CSS was well correlated with swimming velocity corresponding to 4 mmol.l-1 of blood lactate concentration and could avoid using lactate testing. Furthermore, the concept of a critical stroke rate defined as 'the stroke rate value, which can be theoretically maintained continuously indefinitely without exhaustion' and expressed, as the slope of the regression line between the number of stroke cycles and time seemed to be reliable. Coaches, in order to set not only aerobic training loads but also to control swimming technique, could easily use CSS and CSR.